UPAYA MENGATASI KESULITAN SISWA PADA MATERI SEGITIGA DI MTS TANWIRIYAH KALISARI BERDASARKAN TINGKAT KEMAMPUAN SISWA - Abdur Rohim; Isma Hadiyatul Wayiya (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
This research is based on the findings of researchers about the students’ difficulties in the triangle material. Triangle material has been introduced since the elementary school level but what is different is the level of difficulty, triangle material in class VII MTs has led to abstract knowledge. This study aims to identify the difficulties of grade VII students in the triangle material and efforts to overcome them. Qualitative method accompanied by a descriptive analysis approach is the method used in this study. Sources of data taken were class VII mathematics teachers and students. The sample used was 25 students who were then asked to work on test questions. After that grouped based on the level of student ability. The result of this research is that students with very low and low ability criteria cannot understand questions, give reasons, and apply numbers. Efforts to overcome them are scaffolding, increasing self-confidence, giving assignments, class contracts, using appropriate media and methods. Students with sufficient ability level criteria have not been able to solve questions and explain answers. Efforts to overcome this by giving additional assignments, scaffolding and provoking questions. Students with high criteria have not been able to solve questions and are less thorough. Efforts to overcome this by giving additional assignments, scaffolding and asking students to be more thorough. Students with very high criteria have not been able to complete the questions on time. The solution is to give additional tasks to be more skilled.